Seismic reservoir characterization: A feasibility study using seismic site survey data for shallow gas pilot project in Peninsular Malaysia / Haslina Mohamed - Haslina , Mohamed (2018)
Exploration Malaysia of PETRONAS Carigali Sdn Bhd (PCSB) recently embarked on a Shallow Gas (SG) project where most of the leads and prospects were identified based on strong seismic amplitude anomalies that satisfied at least one of the conventional Direct Hydrocarbon Indicator (DHI) criteria. However, the strong amplitude anomalies can be due to low saturation gas, silty gas sand, high porosity brine sand and overpressure sand. This non-uniqueness in the interpretation of the seismic amplitude anomaly has made the SG project a challenging task and hence the needs for this research study. Well log and seismic data are acquired by PCSB specifically for unconsolidated clastic sediments at shallow-depth were made available for the study. The sonic logs were acquired using a new Acoustic Sonic Tool (AST) and the input seismic was from a high resolution 2D site survey which was reprocessed into a pseudo 3D data. Since there is limited literature and suitability of pseudo 3D seismic site survey data for seismic reservoir characterization analysis are still unknown, this research aimed at studying the feasibility of using these input data to: 1) understand the relationship of rock type, porosity, water saturation and pressure to the elastic properties; 2) ascertain the suitability of site survey data for AVO and Inversion study at shallow clastics depth interval; and 3) predict lithology, porosity, and if possible water saturation and reservoir pressure through forward modelling and inversion. To achieve the aim, the following activities were executed in four phases: 1) input data QC and conditioning; 2) elastic logs and seismic forward modeling; 3) seismic inversion processing; and 4) seismic reservoir characterization analysis and interpretation. The results are encouraging. The elastic in situ and modeled elastics logs showed good trend match with the global AI-Vp/Vs crossplot. The established AI-Vp/Vs from the GD-1 well produced clear understanding of elastic properties changes to rock type, hydrocarbon phase, porosity, water saturation and pore pressure. Seismic forward model analysis result clearly demonstrated that seismic amplitude from unconsolidated shallow sand is highly sensitive to gas fill, followed by hydrocarbon saturation, porosity, volume of clay and pore pressure. An excellent well to seismic tie with stable wavelet produced consistent AVO response between the synthetic seismic and observed seismic response thus indicating that both datasets are suitable for seismic inversion processing. High correlation value of 80 - 90% match between inverted AI - Vp/Vs trace and measured AI - Vp/Vs logs confirmed the input site survey seismic data are feasible for seismic reservoir characterization analysis. The predicted sand results match the well result, and the interpreted sand fairway is consistent with shallow marine sand deposition. It is therefore concluded that the pseudo3D seismic site survey data are feasible for seismic reservoir characterization interpretation and analysis. Value of site survey seismic data for seismic reservoir characterization in shallow-depth clastics has been demonstrated here. It is recommended to apply this scheme to other areas so as to improve confidence in drilling shallow gas prospect and especially placing wells at optimal drilling locations.